Determinants of Anemia in The Third Trimester of Pregnancy in Mojokerto - Dian Irawati; Agustin Dwi Syalfina; Sari Priyanti; Geofrey Ssekalembe (Jurnal Berkala Epidemiologi, 2021)
Background: Anemia is a pregnancy complication that increases the morbidity and mortality of mother and baby during pregnancy and until puerperium. In 2015, the incidence of anemia in Indonesia was 23%. Purpose: The aim of this study was to determine factors that influence anemia in the third trimester of pregnancy. Methods: The study was conducted on pregnant women in Mojokerto. This study used a case-control design. The sample calculation results obtained 70 cases and 70 controls. The primary and secondary data were obtained from the MCH book and from interviews conducted according to questionnaire guidelines. Data were analyzed via chi-squared test and logistic regression test. Results: The factors that influence anemia in the third trimester of pregnancy were found to be age (p value = 0.04; OR 2.08; 95% CI = 1.04–4.16), occupation (p value = 0.02; OR = 2.27; 95% CI = 1.15–4.47), birth interval (p value = 0.03; OR = 2.25; 95% CI 1.08-4.69), nutritional status (p value = 0.02; OR = 2.33; 95% CI = 1.14- 4.82), knowledge [about anemia] (p value = 0.01; OR = 3.17; 95% CI = 1.41-7.09), income per month (p value = 0.03, OR = 2.25; 95% CI =1.08–4.69), smoking activity (p value = 0.04; OR = 2.00; 95% CI = 1.02–3.92), perception (p value = 0.02; OR = 2.20; 95% CI = 1.10–4.40) , and spousal support (p value = 0.01; OR = 2.63; 95% CI = 1.16 – 5.93) Conclusion: The most influential factors on anemia in the third trimester of pregnancy were birth interval, nutritional status, and knowledge.